The Impact of Oil Palm Plantations on Economic Growth in Kalimantan and Its Effect on Poverty - Januar Barkah; Muhammad Rojali (Riviera Publishing, 2024)
Oil palm plantations have become a strategic sector in the Indonesian economy, especially in the Kalimantan region. Although its contribution to economic growth is undeniable, its impact on poverty alleviation is still debatable. This study aims to evaluate the relationship between oil palm plantation area and production on economic growth and poverty levels in Kalimantan. The research methodology uses multiple linear regression analysis with secondary data obtained from official statistical reports during the period 2021 to 2022. The independent variables in this study are land area and oil palm production, while the dependent variables include economic growth rates and poverty rates. The results of the study show that the area of oil palm plantations has a significant positive effect on economic growth in Kalimantan, while oil palm production does not show a significant relationship with the decline in poverty rates. This finding indicates that economic growth resulting from the expansion of plantation land does not directly improve the socio-economic conditions of local communities. The implications of this study highlight the importance of more inclusive development policies, with a focus on a more equitable distribution of economic benefits and investment in social infrastructure such as education and health. This is necessary to ensure that the economic benefits of the palm oil sector can be felt by all levels of society, thus supporting sustainable development in Kalimantan.